Ways To Develop Organizational Skills For Future Leaders - Jakhona Karimova Oktamjon qizi (Zien Journals, 2021)
This article describes the problems that arise in the organization and modern solutions to them in a modern way. Here are ten key rules for future organization leaders and their life examples.
Keywords: leaders; organizing a workplace; employees; skills